Bottom‐Up Synthesis of Metallic CoNi Nanoplatelets with Magnetic Vortex‐Like Spin Configurations - Mena‐Alexander Kräenbring; Konstantin Bomm; Georg Bendt; Hanna Pazniak; Benjamin Zingsem; Thomas Feggeler; Sebastian Wintz; Simon Kempkens; Marina Spasova; Stephan Schulz; Michael Farle; Ulf Wiedwald (Small Science, 2025)
Magnetic nanoplatelets hold significant potential for various technical applications due to their ability to switch between a fully magnetized state with high magnetization and a vortex‐like configuration that eliminates stray fields in the absence of an external field. This study presents the synthesis of uniform CoNi nanoplatelets through the topotactic reduction of metal hydroxides using hydrogen plasma. The reduction process is analyzed via magnetometry, leveraging the transition from paramagnetic hydroxide to ferromagnetic metal. Lorentz transmission electron microscopy and scanning transmission X‐ray microscopy confirm the presence of magnetic vortex‐like structures in isolated Co0.85Ni0.15 nanoplatelets at ambient temperature. Additionally, micromagnetic simulations are conducted to further explore the magnetic properties of the nanoplatelets, revealing the formation of magnetic vortex remanent states at diameters between 200 nm and 1 μm and a thickness of around 12 nm. Notably, structural defects and thickness variations do not directly destabilize the magnetic vortex configurations.